Dimensionality of speech fluency: Examining the relationships among complexity, accuracy, and fluency (CAF) features of speaking performances on the Aptis test. (October 2021) - Yan, Xun; Kim, Ha Ram; Kim, Ji Young
Speech fluency has been extensively researched as a core construct for second language (L2) speaking assessment. Despite the broad consensus on its multifaceted nature, few researchers have empirically explored the dimensionality of this construct. Operationalizations of fluency vary across research and practice, using both holistic and fine-grained features. To address the dimensionality of speech fluency, in this study we examined an array of fluency features of speaking performances on the Aptis test. We conducted both univariate and multivariate statistical analyses to investigate the relationship between individual fluency features and language proficiency, as well as the relationships among fluency, complexity, and accuracy features. We found differences in the holistic and fine-grained fluency features, suggesting that they might reflect different dimensions of speech fluency and be associated with different components of language proficiency. Based on the findings, we labeled these two types of fluency features as macro and micro fluencies. Whereas macro fluency features tend to entail a holistic representation of fluency, micro fluency features tend to be more closely related to the automatic processing of lexico-grammar, constituting a more direct reflection of the cognitive processes in speech production. The findings support the multidimensionality of speech fluency and the need to include both macro and micro fluency features in the scoring, scale development, and validation of L2 speaking assessment.